INOVASI PEMBELAJARAN FIQIH MELALUI PROJECT BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA MADRASAH TSANAWIYAH - Fikri Arrazama, M. (As-Sulthan Journal of Education, 2025)
This study aims to describe the implementation of the Project Based Learning (PjBL) model in improving students’ learning outcomes in Fiqh among grade VIII A students at a madrasah tsanawiyah. The research employed a Classroom Action Research (CAR) approach conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. Data were collected through observation, tests, and documentation. Observation was used to record teacher and student activities, tests were conducted to obtain data on learning outcomes, and documentation was used to capture the learning process. The average mastery score in the first cycle was 57%, which increased to 96% in the second cycle. These findings indicate a change in learning outcomes following the implementation of the PjBL model in Fiqh learning.